ICEAP Proceeding Book Vol 2 2018
DOI: 10.26499/iceap.v2i1.91
|View full text |Cite
|
Sign up to set email alerts
|

Theories into Practices: Bloom’s Taxonomy, Comprehensive Learning Theories (CLT) and E-Assessments

Abstract: The development of novel and innovative technologies to an extent has enriched the means of how assessments are done. Researchers and academics alike explore and leverage on the employment of an assemblage of technologies to design their assessments which are critical in gauging the students' learning outcomes. However, the manifestation of technology in the context of teaching and learning necessitates reconceptualization of existential and fundamental theories which scaffold learning process. Thus, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Nonetheless, numerous studies reported positive repercussions on the pedagogically more innovative and engaging, technological augmented deliveries, which have brought upon positive motivation, immediacy and interaction within the landscape of teaching and learning (Crawford, 2017;Halili, 2019;Mahmud, 2018). Deliberating on similar findings, it was reported that students felt more motivated and had better attitudes towards learning (Sundgren, 2017;Mahmud et al, 2019;Bernacki et al, 2020;Stephens & Coryell, 2020), thus contributing to one of the important attributes to the success of computer-assisted environments. With the succinct background illustrated and disparity of knowledge established, this study employs a self-designed survey, developed based on theoretical foundations of the identified variables to answer the following questions:…”
Section: Introductionmentioning
confidence: 72%
“…Nonetheless, numerous studies reported positive repercussions on the pedagogically more innovative and engaging, technological augmented deliveries, which have brought upon positive motivation, immediacy and interaction within the landscape of teaching and learning (Crawford, 2017;Halili, 2019;Mahmud, 2018). Deliberating on similar findings, it was reported that students felt more motivated and had better attitudes towards learning (Sundgren, 2017;Mahmud et al, 2019;Bernacki et al, 2020;Stephens & Coryell, 2020), thus contributing to one of the important attributes to the success of computer-assisted environments. With the succinct background illustrated and disparity of knowledge established, this study employs a self-designed survey, developed based on theoretical foundations of the identified variables to answer the following questions:…”
Section: Introductionmentioning
confidence: 72%
“…However, the continuous assessment became a practice over a period of time. Higher-order thinking skills and practical implementation became the most important components in evaluation with a lot of people considering Bloom's taxonomy as an important model to map the educational learning (Mahmud et al, 2019). Also, with the largescale proliferation of the internet, e-assessments started becoming an important component.…”
Section: Identifying Evaluation Criteriamentioning
confidence: 99%
“…However, knowledge development should be based on the theory of Bloom to scaffold the learning process. The theory consists of six major categories: knowledge, comprehension, application, analysis, synthesis, and evaluation [31]. An example of Yale New Haven Hospital (YNHH), which was an early adopter of the Rothman Index-a tool that reflected patient acuity and riskhas now found its performance positively influenced by nursing assessment data, indicating significant potential for nurses to impact patient care [32][33][34].…”
Section: Introductionmentioning
confidence: 99%